Effectiveness of micro and nano sized propolis with calcium hydroxide combination in inhibiting the formation of Lactobacillus acidophilus biofilm - Derice Putri Nourah Serena; Ira Widjiastuti; Setyabudi; Febriastuti Cahyani; Devi Puspitasari; Tiara Dyah Iswari; Suardita, Ketut; Daniyal Lazuardi Ramadhan (Conservative Dentistry Journal, 2025)
Background: Lactobacillus acidophilus is involved in secondary caries that can accelerate demineralization of the tooth surface. Bacteria forms biofilm as part of a defense mechanism. One of the caries treatments is direct pulp capping with calcium hydroxide (Ca(OH)2) as the gold standard. Due to its high pH, calcium hydroxide can induce necrosis of pulp tissue when it comes into direct contact. Propolis is a natural material produced by honey bees. Propolis has many benefits including antibacterial effects. Nanoparticles are microscopic particles measuring 1-100 nm, reducing particle size can increase the rate of dissolution and absorption. Purpose: This study aims to prove the difference in the biofilm inhibitory ability of a micro and nano-sized combination of propolis and Ca(OH)2 against L. acidophilus biofilms. Methods: This study used true experimental laboratories research with treatment groups that included a control, combination of micro-sized propolis and Ca(OH)2 and combination of nano-sized propolis and Ca(OH)2. Results: The results showed that there was a significant difference between the micro and nano-sized combination of propolis and Ca(OH)2 in inhibiting biofilm growth, with the combination of nano-sized propolis and Ca(OH)2 showing higher effectiveness compared to the micro-sized one. The combination of nano-sized propolis and Ca(OH)2 produced an inhibition value of 84.35%, while the micro-sized one produced an inhibition value of 77.18%. Conclusion: The combination of nano-sized propolis and Ca(OH)2 had a greater biofilm inhibition compared to the combination of micro-sized propolis and Ca(OH)2.